-4/(7y+9)=9/(7y-4)

Simple and best practice solution for -4/(7y+9)=9/(7y-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4/(7y+9)=9/(7y-4) equation:


D( y )

7*y+9 = 0

7*y-4 = 0

7*y+9 = 0

7*y+9 = 0

7*y+9 = 0 // - 9

7*y = -9 // : 7

y = -9/7

7*y-4 = 0

7*y-4 = 0

7*y-4 = 0 // + 4

7*y = 4 // : 7

y = 4/7

y in (-oo:-9/7) U (-9/7:4/7) U (4/7:+oo)

-4/(7*y+9) = 9/(7*y-4) // - 9/(7*y-4)

-4/(7*y+9)-(9/(7*y-4)) = 0

-4/(7*y+9)-9*(7*y-4)^-1 = 0

-4/(7*y+9)-9/(7*y-4) = 0

(-4*(7*y-4))/((7*y+9)*(7*y-4))+(-9*(7*y+9))/((7*y+9)*(7*y-4)) = 0

-4*(7*y-4)-9*(7*y+9) = 0

-91*y-65 = 0

(-91*y-65)/((7*y+9)*(7*y-4)) = 0

(-91*y-65)/((7*y+9)*(7*y-4)) = 0 // * (7*y+9)*(7*y-4)

-91*y-65 = 0

-91*y-65 = 0 // + 65

-91*y = 65 // : -91

y = 65/(-91)

y = -5/7

y = -5/7

See similar equations:

| 2(x-1)+3=7 | | 8x/3x+2 | | 4x+10=25-2x | | 5/6x+8/9=7/9x | | x-3*3=6 | | 5x+14x=152 | | .5x+3=4x-7 | | 4x-2=x-4 | | x^3-4x-16=0 | | 4=n(5n-9) | | x-3*0=6 | | 5=n(5n-9) | | 5n=n(5n-9) | | 13=v+5+5 | | tn=n(5n-9) | | x(x+2)=158 | | 5x+9=3x+3 | | 9x^2-54x=-69 | | x-2*3=-6 | | x-2*0=-6 | | -16x^2+22x+100=80 | | -2(7x+1)=6(1-3x)+2 | | 9=y/x | | -(3y+2)-(-2y-4)=-3 | | 4B-7=15 | | 4AB-7A=15A | | 9=x/y | | 36x^2=3600 | | a+6/3=a/2 | | Y=-3/5x+7 | | 4y-9-5y+12=0 | | 3x+4x=-77 |

Equations solver categories